Inhibition of HDAC6 With CAY10603 Ameliorates Diabetic Kidney Disease by Suppressing NLRP3 Inflammasome - Hou, Qing; Kan, Shuyan; Wang, Zhuang; Shi, Jinsong; Zeng, Caihong; Yang, Dahai; Jiang, Song; Liu, Zhihong (Frontiers in Pharmacology, 2022)
Background: Diabetic nephropathy (DN) is one of the leading causes of chronic kidney disease (CKD) worldwide, tubular injury is the driving force during the pathogenesis and progression of DN. Thus, we aim to utilize the connectivity map (CMap) with renal tubulointerstitial transcriptomic profiles of biopsy-proven DN to identify novel drugs for treating DN. Methods: We interrogated the CMap profile with tubulointerstitial transcriptomic data from renal biopsy-proven early- and late-stage DN patients to screen potential drugs for DN. Therapeutic effects of candidate drug were assessed in Murine model of diabetic kidney disease (STZ-induced CD-1 mice), and HK-2 cells and immortalized bone marrow-derived macrophages (iBMDMs). Results: We identified CAY10603, a specific inhibitor of histone deacetylase 6 (HDAC6), as a potential drug that could significantly reverse the altered genes in the tubulointerstitial component. In DN patients and mice, upregulation of HDAC6 was mainly observed in renal tubular cells and infiltrated macrophages surrounding the diluted tubules. In both early- and late-onset diabetic mice, daily CAY10603 administration effectively alleviated renal dysfunction and reduced macrophage infiltration, tubular injury and tubulointerstitial fibrosis. Mechanistically, CAY10603 suppressed NLRP3 activation in both HK-2 cells and iBMDMs. Conclusion: CAY10603 exhibited therapeutic potential for DN by suppressing NLRP3 inflammasome activation in both tubular cells and macrophages.